Health Outcomes Related to Multiple Exposures in Occupational Settings: A Review - Cassandra Barbey; Nathalie Bonvallot; Frédéric Clerc (Safety and Health at Work)
Individuals are constantly exposed to hazardous factors that can affect their health, the hazards encountered in the workplace can lead to the development of occupational diseases. Risk mitigation measures help to reduce the risks, but they are often designed without consideration of interactions between occupational exposures. Therefore, there is a need for research and it resulted in international research plans and programmes. The aim of this scoping review is to provide an overview of the scientific results related to the link between multiple occupational exposures and human health outcomes. Sixty-three articles were reviewed. Research articles were included only if they mentioned: several combined exposures, the direct characterisation of each exposure, and exposure/health outcome associations. Seven activity sectors were identified: ‘extraction and energy production and distribution’, ‘health care’, ‘banks, public administration and defence’, ‘chemical production’, ‘manufacturing industry’, ‘agriculture and food industry’ and ‘transport and logistics’. Six multiple exposures scenarios were identified: chemical (n = 35), chemical/physical-biomechanical (n = 22), chemical/psychosocial-organisational (n = 6), physical-biomechanical (n = 9), physical-biomechanical/psychosocial-organisational (n = 13), and psychosocial-organisational (n = 12). The health problems identified concern nervous, mental, respiratory, musculoskeletal, auditory and other systems. Eighty-eight of 97 (91%) multiple exposure/health problem associations were reported to be statistically significant. Twenty studies (32%) provided specific risk prevention advice for multiple exposures. Prevention aimed at reducing risks to workers' health is still underdeveloped, further research is needed to improve prevention methods. No study was related to biological risk, and some other multiple exposures known to have health effects were not identified as well. This highlights the need for more multiple exposures research.